(untitled) (Al-Mansour Journal, 2023)
Every state all over this world can’t survive and keep on achieving its project withoutkfinancial income.Even the existence of all states rely on bases of finance .various types of government cant keep on with their activities without considering their financial affairs ,whether in simple state or composite state , unified ,because the need to revenues is the main point for all forms of the states. But the important thing we will discuss is how will be the allocation of income in federal states, this matter may raise many problems, and issues that might rise conflicts, and enter the crossroads that we should choice one of them. More over the important of this topic seems as result of the federal shape which Iraq adopted. Therefore we must research about this changing because it is a new move whether in political or financial field in Iraq to avoid any mistake in application. It is well known to reader what we mean by federalism as form of governance where the authorities are constitutionally divided between central government and smaller units (provinces, states) .in other words optional union between the states of the federated states, lead to its transformation to a single legal or political system and with the retention of these parts of the united personal privacy and identity, and there is delegation of the central union of some of the joint powers authority with the retention of some of these parts or the states . And thus we note that retain include the power of legislative, executive and independent judiciary within the constitutional sphere, is well known, the possibility of the adoption of the central government fiscal policy to reduce the competence of states in various ways, including the granting of aid, whether conditional or no, even to financing of projects or to fill the provinces deficit in its treasury, or other needs. In order to avoid the difficulties and problems mast follow the federal constitution , the foundation upon which all the institution of the state are depend and built their respective responsibilities , and thus may provide more explicit on how the allocation of revenues between the state and federal provinces . On the other hand, highlights role of the state budget, as is general budget of the federal state, which is the method of organization of state revenues and expenditures, and thus is an essential tool for the organization of the provinces quota of income, contribute the executive and the legislative as representative of people to developed and approved the state by it. There are many reasons which may be taken into consideration when determining the quotas, one of these factors is the contribution of the state in federal state in general, and the possibilities of each state and its own resources that can be used as private resources, as well as geographic and environmental differences, differences in population … Thus, we can in accordance that principles find ways to allocate the federal state revenues.